Petrology and U-Pb Zircon Geochronology of Amphibole-rich Cumulates with Sanukitic Affinity from Husky Ridge (Northern Victoria Land, Antarctica): Insights into the Role of Amphibole in the Petrogenesis of Subduction-related Magmas - Tiepolo, Massimo; Tribuzio, Riccardo (Journal of Petrology, 2008)
A microanalytical trace element and geochronological study was carried out on mafic amphibole-rich cumulates (quartz diorites) cropping out in northern Victoria Land (Antarctica). Associated tonalites and basement rocks were also investigated. Rock textures and major and trace element mineral compositions reveal the presence in quartz diorites of two mineral assemblages: (1) clinopyroxene-I + brown amphibole ± dark mica; (2) clinopyroxene-II + green amphibole + plagioclase + quartz. Both mineral assemblages contain mafic phases with elevated Mg-number, but their trace element signatures differ significantly. In situ U–Pb zircon geochronology was carried out to support petrogenetic and geological interpretations. Quartz diorites were emplaced in the mid-crust probably at 516 ± 3 Ma. Parental melts of quartz diorites were computed by applying solid/liquid partition coefficients. The melt in equilibrium with the first mineral assemblage (melt-I) is extremely depleted in heavy rare earth elements (HREE), Y, Ti, Zr and Hf (at about 0·2 times normal mid-ocean ridge basalt) and enriched in B, Th, U, the large ion lithophile elements and light REE (LREE). It shares many similarities with sanukitic melts (e.g. Setouchi andesites), which originated by equilibration of subduction-derived sediment melts with a refractory mantle. The melt in equilibrium with the second mineral assemblage (melt-II) is characterized by a steep LREE enrichment (La N /Yb N up to 39), a U-shaped HREE pattern and low Ti, which is depleted relative to HREE. The trace element signature of melt-II can be acquired through amphibole crystallization starting from a sanukitic melt similar to melt-I, probably in a deeper magma chamber. Our results allow us to constrain that melts from the subducted slab were produced on a regional scale, in accordance with literature data, below a large sector of the east Gondwana margin during the mid-Cambrian. Implications for the role of amphibole in petrogenesis of subduction-related magmas are also discussed.